2013
DOI: 10.1242/dev.087858
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish rhabdomyosarcoma reflects the developmental stage of oncogene expression during myogenesis

Abstract: SUMMARYRhabdomyosarcoma is a pediatric malignancy thought to arise from the uncontrolled proliferation of myogenic cells. Here, we have generated models of rhabdomyosarcoma in the zebrafish by inducing oncogenic KRAS G12D expression at different stages during muscle development. Several zebrafish promoters were used, including the cdh15 and rag2 promoters, which drive gene expression in early muscle progenitors, and the mylz2 promoter, which is expressed in differentiating myoblasts. profound effects on the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…This is consistent with the differentiation status of RMS cells shown in oncogenic KRAS (G12D) induced zebrafish models of RMS where embryonal RMS cells recapitulate normal myogenesis and their associated migratory and proliferative capacity [42]. Also, targets of these miRNAs in these networks are likely to contribute to these invasive and migratory phenotypes in RMS, for example miR-206 targets the MET tyrosine-kinase receptor which is highly expressed in RMS and enhances RMS cell migration [24].…”
Section: Discussionsupporting
confidence: 73%
“…This is consistent with the differentiation status of RMS cells shown in oncogenic KRAS (G12D) induced zebrafish models of RMS where embryonal RMS cells recapitulate normal myogenesis and their associated migratory and proliferative capacity [42]. Also, targets of these miRNAs in these networks are likely to contribute to these invasive and migratory phenotypes in RMS, for example miR-206 targets the MET tyrosine-kinase receptor which is highly expressed in RMS and enhances RMS cell migration [24].…”
Section: Discussionsupporting
confidence: 73%
“…To assess roles for myf5 in regulating ERMS growth, we transgenically expressed myf5 under control of the differentiated myosin light chain muscle promoter ( mylpfa ). This transgene faithfully drives expression in terminally-differentiated muscle cells in both transient and stable transgenic fish (Xu et al, 1999; Langenau et al, 2007; Ignatius et al, 2012; Storer et al, 2013; Chen et al, 2014) and has been used to identify zebrafish ERMS cell subfractions that lack myf5 , have low proliferative capacity, cannot self-renew, and do not sustain ERMS growth in vivo (Ignatius et al, 2012). Here, rag:kRAS G12D was co-injected with mylpfa:myf5 into one-cell-stage zebrafish and analyzed for tumor onset.…”
Section: Resultsmentioning
confidence: 99%
“…Tumors were histologically staged based on differentiation (Storer et al, 2013; Figure 1—figure supplement 2). As reported previously, primary kRAS G12D - induced ERMS were comprised of 50% undifferentiated stage 1 ERMS (N = 5 of 10, Figure 1B,C and Figure 1—figure supplement 2), which harbored mostly small round blue cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the authors concluded that the zERMS progenitor is an activated satellite cell. In a complementary study, KRAS G12D was conditionally expressed in cells at different stages of myogenic differentiation to identify zebrafish cell types that are permissive for zERMS 119 . KRAS G12D expression was regulated by either the rag2 or cdh15 (which encodes m-cadherin) promoters, which are active in early muscle progenitors, or by myosin light chain 2 ( mylz2 ; also known as mylpfa ), which is expressed in differentiating myoblasts.…”
Section: Interrogating the Cellular Origins Of Rmsmentioning
confidence: 99%